IMPACT OF ORGANIC MATTER ON THE GROWTH OF JATROPHA CURCAS AND MORINGA OLEIFERA SEEDLINGS BENEATH WATER DEFICIT - Amal El-Gamal; Mohamed Hesham Khamis (Scientific Journal of Flowers and Ornamental Plants, 2021)
A field experiment was carried out in order to determine the proper irrigation rate and the best organic matter in a loamy sand soil to optimize the growth, biomass, and chemical composition of the seedlings of Jatropha curcas (poisonnut) and Moringa oleifera (horseradishtree). Three irrigation deficits (100, 75, and 50% of field capacity F.C.) and three organic substance treatments [control, compost, and humic acid (HA)] were implemented in a split-plot design. Generally, increasing the irrigation deficit from 100% to 50% of F.C. decreased growth and biomasses for both plants. The 75% F.C. was the better treatment that enhanced the growth and biomasses parameters of J. curcas seedlings. Contrarily, HA exceeds compost in increasing these growth parameters but compost and HA were alike for increasing shoots (fresh and dry weights) and decreasing roots biomasses. HA and compost under 100 and 75% F.C. were significantly similar to the decreased roots biomass, as well as, the S:R ratio of J. curcas seedlings.The results revealed that regardless of their effects and mechanism to resist drought, both J. curcas and M. oleifera are well adapted to semi-arid regions when amended with HA or compost, under irrigation deficit 75% of F.C.